Pengaruh kualitas produk dan harga terhadap keputusan pembelian: peran minat beli sebagai variabel moderating - Sandro Christian (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2018)
This study aims to determine how much influence the quality of products and prices on purchasing decisions and the purchase interest as a moderating variable. This research is a quantitative study using the SPSS Statistics 22 program with a total sample of 72 respondents who used futsal specs in Jabodetabek who had bought futsal specs using non-probability sampling and purposive sampling techniques. The results of this study indicate that the factors that influence purchasing decisions are product quality. Buying interest moderates the relationship of all independent variables with the dependent variable. The implications of this research can be a reference for the management team in formulating futsal shoes sales strategy related to product quality, price, buying interest.